1984
DOI: 10.1038/310207a0
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence and expression of the B95-8 Epstein—Barr virus genome

Abstract: The complete (172,282 base pairs) nucleotide sequence of the B95-8 strain of Epstein-Barr virus has been established using the dideoxynucleotide/M13 sequencing procedure. Many RNA polymerase II promoters have been mapped and the mRNAs from these promoters have been assigned to the latent or early/late productive virus cycles. Likely protein-coding regions have been identified and three of these have been shown to encode a ribonucleotide reductase, a DNA polymerase and two surface glycoproteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
1,178
2
2

Year Published

1989
1989
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,951 publications
(1,204 citation statements)
references
References 60 publications
10
1,178
2
2
Order By: Relevance
“…The cloning of genes or cDNAs for UDGs from bacteria [40], yeast [41], the fish Xiphophorus [42], mouse [43] and human cells [43,44] and several herpes viruses [45][46][47][48][49][50][51][52] has demonstrated a striking similarity between these enzymes, ranging from 40.3 % (yeast) to 90 % (mouse) amino acid identity relative to human UDG. The similarity is confined to several discrete boxes.…”
Section: Udgs Belong To a Highly Conserved Ancient Familymentioning
confidence: 99%
“…The cloning of genes or cDNAs for UDGs from bacteria [40], yeast [41], the fish Xiphophorus [42], mouse [43] and human cells [43,44] and several herpes viruses [45][46][47][48][49][50][51][52] has demonstrated a striking similarity between these enzymes, ranging from 40.3 % (yeast) to 90 % (mouse) amino acid identity relative to human UDG. The similarity is confined to several discrete boxes.…”
Section: Udgs Belong To a Highly Conserved Ancient Familymentioning
confidence: 99%
“…On the other hand a 40 Kb DNA fragment (named p31) including the BamH1 D to BamH1 A regions of EBV genome, has been found able to immortalize epithelial cells from African green monkey kidney (Gri n and Karran, 1984) and marmoset or human fetal kidney (Karran et al, 1990). Among about 20 ORFs (Open Reading Frames) localized in this 40 kb fragment (Baer et al, 1984), BARF0 and BARF1 were reported to be expressed in biopsies from NPC patients (Hitt et al, 1989;Sbih-Lammali et al, 1996), suggesting that either or both ORFs might be involved in epithelial cell immortalization process. We have previously shown that BARF1 ORF expression induced tumorigenic transformation in either the rodent ®broblast line Balb/c 3T3 (Wei and Ooka, 1989) or in the human EBV-negative B cell line Louckes (Wei et al, 1994): after injection of BARF1-transfected cells into new-born rats, we observed the development of agressive tumors from the murine ®broblasts, while the Louckes line induced small tumors which disappeared after 3 weeks post-injection.…”
Section: Introductionmentioning
confidence: 99%
“…Homology scores with human collagenase (54) and with the metalloproteinase of Serratia (60) were considerably lower. Interestingly, optimized alignment of fibrolase and BRRFl protein (Baer et al, 1984) shows that the viral protein retains the essential components of the zinc-binding site, including the consensus signature. The significance, if any, of this identity remains to be established, although it raises some intriguing questions concerning symbiotic relationships between viruses and snakes.…”
Section: A Randolph Et Afmentioning
confidence: 99%